PENYUSUNAN PEDOMAN TATA NASKAH DINAS DI LINGKUNGAN BIDANG PENDIDIKAN TINGGI PONDOK PESANTREN SALAFIYAH SYAFI’IYAH SUKOREJO - Maskuri Maskuri; Ach. Zubairi (LP2M Universitas Ibrahimy, 2024)
Here are two communication methods within organizational and institutional communities, namely oral and written communication. Oral communication is commonly carried out by everyone involved in the institution/organization, such as everyday communication without standardized guidelines, not bound normatively, all conducted in a relaxed and familial atmosphere. Meanwhile, written communication is conducted through standardized forms, types, and formats. Official documents serve as a written communication tool to convey information to stakeholders so that what is written can be understood correctly and effectively. Mistakes in composing official documents can result in misunderstandings for the message recipients. Through this assistance, the aim is for all involved parties, especially personnel within the Higher Education Division of Salafiyah Syafi'iyah Islamic Boarding School Sukorejo, along with all its coordinating areas, to understand the protocol for official document drafting. The absence of drafting guidelines prompted us to conduct this assistance. The method used in the assistance implementation involves guidance on technical aspects of drafting official letters, practice in creating official documents in various forms, types, and formats. Additionally, we conducted observations, interviews, and collected necessary official document samples. The expected final outcome is the development of a drafting protocol as a guideline for administrative management. All participants in the training workshops and discussions showed enthusiasm, thus facilitating the tangible realization of the expected official document drafting protocol draft.